Physicochemical Characteristics of Aedes Mosquito Breeding Habitats in Suburban and Urban Areas of Kinshasa, Democratic Republic of the Congo - Mbanzulu, Kennedy Makola; Mboera, Leonard E. G.; Wumba, Roger; Engbu, Danoff; Bojabwa, Michael Mondjo; Zanga, Josué; Mitashi, Patrick Mulopo; Misinzo, Gerald; Kimera, Sharadhuli Iddi (Frontiers in Tropical Diseases, 2022)
Background The knowledge of key elements of the ecosystem affecting mosquito distribution and their population dynamics is essential for designing mosquito-borne disease interventions. The present study characterized the physicochemical properties of Aedes mosquito breeding habitats in Democratic Republic of the Congo. Methods A cross-sectional survey was carried out in Kinshasa, from February to April 2021. The physicochemical characteristics of the natural and artificial aquatic habitats of Aedes were measured using a multiparametric device. Results Out of 438 breeding habitats inspected, 273 (62.3%) contained mosquito larvae. The Aedes mosquitoes identified in 76.19% of positive breeding sites were Aedes albopictus (67.30%) and Aedes aegypti (37.98%). The median values of dissolved oxygen (DO) (1.0), turbidity (19.15), and salinity (0.115) in water breeding sites of Aedes were respectively 0.8, 55.0, and 0.29 in Culex breeding sites (p < 0.05). The physicochemical characteristics of the breeding habitat for Ae. aegypti and Ae. albopictus were almost identical. In urban areas, the median temperature was 29.82 while it was 29.60 in suburban areas (p < 0.05). Significantly, the salinity was higher in bamboo and metal containers while DO was higher in tins. After analysis using simple linear regression, total dissolved solids (r = 0.23; p = 0.000), conductivity (r = 0.23), salinity (r = 0.23), and temperature (r = 0.13) were associated with larval density (p < 0.05). In the final model (r = 0.30, p = 0.01), salinity (r = 0.23) and DO (r = 0.138) adjusted to temperature, pH, and turbidity were associated positively to larvae density. Conclusion The Aedes breeding sites and mosquito density were significantly influenced by water salinity, DO, temperature, pH, and turbidity.